National Celebrations from an Outsider's Perspective - Alempijevic, Nevena Skrbic (Tidsskrift for kulturforskning, 2008)
The focus of this paper is the social memory dimension of May 17th, the Norwegian Constitution Day, as organized and acted out in Bergen in 2005. The celebrations are approached through Pierre Nora's concept of "realms of memory". The author places emphasis on the participants' sensory and bodily experiences. She also discusses the way her outsider's gaze into May 17th reflects the way she experienced national holidays in Croatia. The event is perceived from two different perspectives: by following in the footsteps of the main organizers, the May 17th Committee members, and by experiencing the day in the company of members of a family living in Bergen. In that way the author obtained some insight into the official discourse about May 17th, as well as into one private interpretation of the occasion. For these informants, rememberance and the national component played a significant part of their celebrations. The author concludes that not only motifs relating to 1814, the year of the drafting of the new constitution at Eidsvoll, were noticeable at the celebrations. Motifs evoking the Viking era and WW2 were also present. This is why the author concludes that it is the glorious past that societies remember during contemporary May 17th celebrations.